Population health science as a unifying foundation for translational clinical and public health research. (June 2022) - Cullen, Mark R.; Baiocchi, Michael; Chamberlain, Lisa; Chu, Isabella; Horwitz, Ralph I.; Mello, Michelle; O'Hara, Amy; Roosz, Sam
Abstract: Separated both in academics and practice since the Rockefeller Foundation effort to "liberate" public health from perceived subservience to clinical medicine a century ago, research in public health and clinical medicine have evolved separately. Today, translational research in population health science offers a means of fostering their convergence, with potentially great benefit to both domains. Although evidence that the two fields need not and should not be entirely distinct in their methods and goals has been accumulating for over a decade, the prodigious efforts of biomedical and social sciences over the past year to address the COVID-19 pandemic has placed this unifying approach to translational research in both fields in a new light. Specifically, the coalescence of clinical and population-level strategies to control disease and novel uses of population-level data and tools in research relating to the pandemic have illuminated a promising future for translational research. We exploit this unique window to re-examine how translational research is conducted and where it may be going. We first discuss the transformation that has transpired in the research firmament over the past two decades and the opportunities these changes afford. Next, we present some of the challenges —technical, cultural, legal, and ethical— that need attention if these opportunities are to be successfully exploited. Finally, we present some recommendations for addressing these challenges. Highlights: Population datasets with extensive biologic, medical and social information augur a new approach for translational research. Important questions about health throughout the life course could be answered were relevant person-level data accessible. Technical, cultural, and legal constraints presently limit the ability to actualize this vision. Analysis of these limitations in the context of the recent pandemic reveals each could be overcome with proper attention.